Sourcing Local and Sustainable Tourism: The Case of Yesilyurt - Yıldız, Özay Emre (International Journal of Contemporary Economics and Administrative Sciences, 2018)
Once tourism establishments in the destination choose to source their food & beverage stocks locally, this will cause remarkable changes for all parties involved. The small-scale producers will benefit increased demand and income and also find opportunities to diversify economic activities. The establishments will increase the quality of their food & beverage offer and lower their costs. The tourists will enjoy a more authentic and memorable experience. The destination will see higher multiplier effect and lower leakage, preservation of nature and culture, and a potential for a marketable brand image and regional identity, as well as product diversification. The decision has the potential to contribute to sustainability of the destination however, only if the local food & beverage and supporting cultural and natural elements are in coherence, to create a sense of place.